G326(P) Facial weakness in children: It's not bell's when alarm bells are ringing. (27th April 2016) - Ram, D; Aziz, M; Vassallo, G
Abstract : Introduction: An initial manifestation of isolated facial weakness is commonly due to Bell's palsy. We describe three cases of paediatric stroke presenting as facial weakness, posing a challenge to medical practitioners in interpreting clinical signs and delaying diagnosis. Cases: Patient 1 is 15 year old boy who presented to his local emergency department with a right-sided facial droop and was discharged with a diagnosis of Bell's palsy. The pattern of facial nerve weakness was not documented. Over the next 48 h during a camping trip, his parents noticed weakness of his right arm and he was rushed to a different emergency department. Brain imaging confirmed a left MCA infarct secondary to left ICA dissection. Patient 2 is a 4 year old boy who presented to his local emergency department with a four day history of right-sided facial weakness. He was diagnosed with Bell's palsy and discharged with prednisolone and aciclovir. Over the next 24 h, he became encephalopathic with right arm weakness and re-presented. Urgent brain imaging demonstrated an acute left MCA infarct. Patient 3 is a 4 year old girl who presented to her GP with mild encephalopathy a few days after the onset of a viral illness. She developed an asymmetrical smile, which was presumed to be due to Bell's palsy. Over the next week, it was noted that the use of her right arm was suboptimal and subsequent brain imaging confirmed a left MCA infarct. Discussion: In all cases, the diagnosis of stroke was not contemplated and the facial weakness was dismissed as the much commoner Bell's palsy. Documentation on the pattern of weakness was absent in all three cases. Careful examination differentiating upper and lower motor neurone features will help distinguish stroke from Bell's palsy. Conclusion: Our cases illustrate that stroke is an important condition to consider in children presenting with any form of acute neurological deficit, including facial weakness. Increased awareness amongst primary and secondary healthcare professionals is needed to ensure that the diagnosis of stroke is not delayed in these situations.